The global stress response regulator oxyS in an adherent-invasive Escherichia coli strain attenuates experimental colitis - Diana Arsene; Sandrine Y. Tchaptchet; Jonathan J. Hansen (Gut Microbes)
Crohn’s disease and ulcerative colitis in humans and experimental immune-mediated colitis in mice are likely due in part to overactive immune responses to resident intestinal bacteria, including certain strains of adherent-invasive Escherichia coli (E. coli) such as E. coli NC101. We have previously shown that specific E. coli NC101 stress responses are upregulated during experimental colitis and attenuate inflammation. However, the roles of broader stress response pathways in E. coli NC101 during experimental colitis are unknown. We hypothesize that the global stress response regulator in E. coli, oxyS, also reduces experimental colitis. We show that intestinal E. coli NC101 upregulate oxyS expression during colitis in monocolonized interleukin-10 deficient mice. Furthermore, we demonstrate that oxyS-sufficient E. coli NC101 have decreased motility and biofilm formation in vitro and attenuated intestinal translocation and colitogenic potential in vivo compared with oxyS-deficient E. coli. These data suggest that activation of a generalized E. coli stress response, oxyS, reduces experimental colitis and may be a potential therapeutic target.